PENGEMBANGAN MEDIA PEMBELAJARAN POWERPOINT PADU MUSIK TERHADAP ANTUSIASME SISWA DALAM PEMBELAJARAN ILMU SOSIAL - A. Ahdar (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2018)
Abstract This study aims to (1) obtain an overview of the use of integrated music powerpoint media in social studies learning (2) obtain a picture of students' enthusiasm in learning social studies with the use of solid music powerpoint media and the use of conventional media (3) obtain an overview of the effect of the use of solid music powerpoint media on enthusiasm to study Social Sciences in Soppeng District. This type of research is a true experiment design experimental study involving one experimental class and one control class, with the design of the pre-test post-test control group design. The hopitesis test results revealed that there was a difference in the level of enthusiasm between the experimental class and the significant control class, so that it could be concluded that there was a significant difference between the level of enthusiasm of the experimental class and control class enthusiasm. Keywords: Powerpoint Development, Social Sciences, Student.